FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH DALAM MEMILIH BANK SYARIAH MANDIRI (STUDI KASUS NASABAH BANK SYARIAH MANDIRI KANTOR CABANG CIBINONG) - Hari Subagyo, Wawan; Wutsqo, Urwatul (Economicus, 2018)
Research aims to understand factors affecting the difference decision-making customers in choosing Bank Syariah Mandiri and to know the key factor of decision making customers in choosing Bank Syariah Mandiri. The data used in this research was primary data obtained by the division of the questionnaire. This Questionnaire consists of nine factors that is social, personal, culture, psychological, location, products, service, facilities and to promote the total number of questions about 19 questions and they are highly capable validity and reliability. Samples to be taken as many as 100 respondents. The method of analysis that used is discriminant analysis. The results of the study showed that of factors affect the difference decision customers in choosing Bank Syariah Mandiri is the variable of the social (0,023), persons (0,027), culture (0,001), and facility (0,046). The key variable from the study is the variable “ culture “ so that can be concluded miscellany.